Análise filogenética e filogeográfica de isolados de Pythium insidiosum através do marcador genético Exo1 e suscetibilidade aos compostos metálicos - Ribeiro, Tatiana Corrêa (2016)
Pythium insidiosum is an aquatic oomycete that causes pythiosis, a pyogranulomatous disease of difficult treatment that infects animals and humans. In Brazil, the disease is often described in horses in the regions of the Pantanal and Rio Grande do Sul. Thailand is an endemic country for human pythiosis, where the disease has important morbidity and mortality rates. Pythiosis presents a rapid progression, there is no standard treatment available and unresponsive cases to chemotherapy are observed. P. insidiosum has no ergosterol in the cellular membrane, and this component is the main target of antifungal drugs currently available. This study aimed to analyze the phylogenetic and phylogeographic characteristics of Brazilian and Thai isolates of P. insidiosum in order to better understand the evolution of this oomycete, as well as to characterize the susceptibility of P. insidiosum against metal compounds in search of new therapeutic alternatives. This study included 16 partial DNA sequences of Exo-1,3-ß-glucanase gene (Exo1) of Brazilian isolates of P. insidiosum, 23 sequences of Thai isolates and 2 standard strains. Phylogenetic analyses employed the methods of maximum parsimony (MP), neighbor-joining (NJ), maximum likelihood (ML), and Bayesian analysis (BA). The phylogeographic analyses involved evaluation of the nucleotide diversity, of polymorphism, of molecular variance (SAMOVA and AMOVA), the degree of genetic diversity (FST) and neutrality tests, which were performed with 31 exo1 the DNA sequences of P. insidiosum with known geographical origin. exo1 demonstrated to be a good marker for phylogenetic and phylogeographic studies. A tree consensus of the four methods was obtained, and observed three distinct groups consistent with previous analyzes with other molecular markers. In the phylogeographic analyses, the Thai isolates display a high diversity, confirming its earlier origin in relation to Brazilian isolates. Structuring patterns were observed among Brazilian isolates, suggesting a recent expansion of these and indicates the need for further studies with larger sample size of these regions. In the evaluation of in vitro susceptibility of P. insidiosum (n = 23) to metallic compounds containing cadmium, lead, copper, manganese, and zinc were performed using microdilution broth test based on document M38-A2. The minimum inhibitory and fungicidal concentrations were established for all isolates. Copper acetate and cadmium acetate showed minimal inhibitory concentration range of 4-64 mg/mL and 16-256 mg/mL, respectively. These results suggest that copper and cadmium can inhibit the growth of P. insidiosum, emphasizing the most inhibitory activity of copper acetate. Furthermore, this study suggests that compounds of copper and/or cadmium can be used in future research to develop effective drugs against P. insidiosum.